The nature of excessive sleepiness and sudden sleep onset in Parkinson׳s disease - Daniel Gurgel Fernandes Távora; Veralice Meireles Sales de Bruin; Romulo Lopes Gama; Emily Mourão Soares Lopes; Iago Farias Jorge; Pedro Felipe Carvalhedo de Bruin (Sleep Science, 2014)
Objectives: Excessive daytime sleepiness (EDS) and sudden sleep onset (SOS) episodes are frequent in Parkinson׳s disease (PD). The objectives are to identify clinical characteristics and factors associated with EDS and SOS episodes. Methods: Clinical demographic data were recorded (N=100, mean age=65.0±10.4). EDS was identified by the Epworth Sleepiness Scale (ESS>10) and SOS episodes were registered. Disease severity was evaluated by the Unified Parkinson׳s Disease Rating Scale (UPDRS, I, II, and III), sleep disturbances by the Parkinson׳s Disease Sleep Scale (PDSS<100), depressive symptoms by the Beck Depression Inventory (BDI>10) and rapid eye movement (REM) sleep behavior disorder (RBD) by the REM sleep behavior scale. Levodopa equivalent dose was measured. Results: PD patients with EDS (67%) were predominately male (73.1%) and had worse disease severity (UPDRS II and III p= 0.005); SOS episodes (39%) were associated with disease duration, diabetes, sleep disturbances (PDSS Scale), disease severity (UPDRS I, II, III) and RBD symptoms (p<0.05). Stepwise regression analysis showed that EDS was independently associated with motor-symptoms severity (UPDRS III scale, p=0.003). SOS episodes were independently associated with disease duration (p=0.006) and sleep disturbances (PDSS scale, p=0.03): patients had more uncomfortable immobility at night, tremor on waking and snoring or difficult breathing. Discussion: EDS and or SOS episodes are frequent and manifest a differential pattern in PD. SOS episodes are associated with longer disease duration, diabetes, sleep disturbances and RBD symptoms indicating that these “sleep attacks” are of multifactorial origin and probably influenced by brain structural abnormalities.